Intelligent robotics and applications : 11th International Conference, ICIRA 2018, Newcastle, NSW, Australia, August 9-11, 2018, proceedings.: 11th International Conference, ICIRA 2018, Newcastle, NSW, Australia, August 9-11, 2018, proceedings. Part II ([2018]) - Unknown
No abstract available